Analysis of content, credibility, and reliability of information on chronic obstructive pulmonary disease treatment in YouTube™ videos: a cross-sectional observational study - Ana Luíza da Silva Nunes Teixeira Rodrigues; Vanessa Kelly da Silva Lage; Redha Taiar; Joyce Noelly Vitor Santos; Laisa Braga Maia; Jousielle Márcia dos Santos; Vinícius Cunha Oliveira; Ana Cristina Rodrigues Lacerda; Vanessa Amaral Mendonça (Fisioterapia e Pesquisa)
ABSTRACT Chronic Obstructive Pulmonary Disease (COPD) is characterized by airway abnormalities, resulting in persistent airflow obstruction. Treatment involves pharmacological and nonpharmacological interventions which are supported by several COPD consensus and guidelines. YouTube can often be used to share information about treatments for chronic diseases like COPD; however, the credibility of such information may not be adequate. This study evaluates the reliability and credibility of information concerning COPD treatment disseminated on YouTube, the most popular social media platform, and assess its alignment with the GOLD guideline. A cross-sectional observational study was conducted to select the first 200 English-language videos on COPD treatment posted on YouTube. Video evaluation used validated instruments, including the DISCERN tool (quality assessment), the Health on the Net Foundation Code of Conduct - HONcode (credibility assessment), and the GOLD guideline (reference). Poor agreement with the GOLD guideline (97.4%) was found. HONcode assessment showed that 75.7% of the videos achieved a high credibility rating. Regarding information quality, 75.7% of the videos received positive ratings based on the DISCERN tool. Despite exhibiting adequate credibility, the analyzed videos displayed fluctuating levels of quality, ranging from medium to low. Moreover, there was limited consensus between the videos and the GOLD guideline. Continuous analysis of such content can be used to ensure dissemination of reliable information on YouTube.